Leach-SX-EW copper revalorization from overburden of abandoned copper mine Cerovo, Eastern Serbia - Stevanović Z.; Antonijević M.; Jonović R.; Avramović Lj.; Marković R.; Bugarin M.; Trujić V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Hydrometallurgical processes for copper revalorization from overburden of abandoned mine Cerovo in Eastern Serbia were studied. Paper contain results of percolation leaching tests, performed with acidic mine waters accumulated in the bottom of the former open pit, followed by solvent extraction (SX) and electrowinning (EW) processes on achieved copper pregnant leach solutions. Usage of accumulated waste waters was objected to minimizing the environmental hazard due to uncontrolled leaking of these waters in nearby creeks and rivers. Chemical composition of acidic mine waters used for leaching tests was: (g/dm3): Cu - 0.201; Fe - 0.095; Mn - 0.041; Zn - 0.026; Ni - 0.0004; pH value - 3.3. Copper content in overburden sample used for leaching tests was 0.21% from which 64% were oxide copper minerals. In scope of leaching tests were examined influence of leaching solution pH values and iron (III) concentration on copper recovery. It was established that for 120 hours of leaching on pH=1.5 without oxidant agents, copper concentration in pregnant leach solutions enriched up to 1.08g/dm3 which was enough for copper extraction from solution with SX-EW treatment. As extraction reagent in SX circuit was used LIX-984N in a kerosene diluent. Cathode current density in electrowinning cell was 220Am-2 while electrolyte temperature was kept on 50±2oC. Produced cathode copper at the end of SX-EW process has purity of 99.95% Cu.